From attachment and support to college students' well-being: a systematic review through the lens of self-determination theory - Chen, Xi; Mohd Khir, Azlina; Hamsan, Hanina Halimatusaadiah; Burhan, Nik Ahmad Sufian (Malque Publishing, 2026)
This systematic review synthesized empirical evidence on the relationships among adult attachment, social support, self-determination and subjective well-being among college students. Following PRISMA guidelines, we systematically searched the Web of Science, Scopus, PsycINFO, and Google Scholar databases (2004-2024), yielding 22 eligible studies (20 cross-sectional, 2 longitudinal). The results indicated that both adult attachment and social support influenced subjective well-being through the satisfaction of basic psychological needs. Secure attachment and high levels of social support were positively associated with subjective well-being, whereas anxious and avoidant attachment styles were negatively associated. The satisfaction of basic psychological needs (autonomy, competence, and relatedness) emerged as a crucial mediating mechanism, with consistent patterns across different cultural contexts, although the sources and effects of social support varied culturally. Despite methodological limitations, including predominantly cross-sectional designs and restricted sample representativeness, this review provides valuable insights for enhancing college students' well-being through improving attachment relationships, strengthening social support networks, and facilitating basic psychological needs satisfaction. Future research should employ more longitudinal designs, expand sample diversity, and examine cultural moderators.